Palliative resection of the primary tumor is associated with improved overall survival in incurable stage IV colorectal cancer: A nationwide population‐based propensity‐score adjusted study in the Netherlands. Issue 9 (12th July 2016) - 't Lam‐Boer, Jorine; Van der Geest, Lydia G.; Verhoef, Cees; Elferink, Marloes E.; Koopman, Miriam; de Wilt, Johannes H.
Abstract : As the value of palliative primary tumor resection in stage IV colorectal cancer (CRC) is still under debate, the purpose of this population‐based study was to investigate if palliative primary tumor resection as the initial treatment after diagnosis was associated with improved overall survival. All patients with stage IV colorectal adenocarcinoma (2008–2011) were selected from the Netherlands Cancer Registry, and patients undergoing treatment with curative intent ( i.e ., metastasectomy, radiofrequency ablation and/or hyperthermic intraperitoneal chemotherapy), or best supportive care were excluded. After propensity score matching, a multivariable Cox proportional hazard model was performed to determine the association between treatment strategy and mortality. From a total group of 10, 371 patients with stage IV CRC, 2, 746 patients (26%) underwent an elective palliative resection of the primary tumor, whether or not followed by systemic therapy, and 3, 345 patients (32%) were initially treated with palliative systemic therapy. After propensity score matching, median overall survival in these groups was 17.2 months (95% CI 16.3–18.1) and 11.5 months (95% CI 11.0–12.0), respectively. In Cox regression analysis, primary tumor resection was significantly associated with improved overall survival (hazard ratio of death = 0.44 [95% CI 0.35–0.55], p  < 0.001). This large population‐based study shows an overall survival benefit for patients with incurable stage IV CRC who underwent primary tumor resection as the initial treatment after diagnosis, compared to patients who started systemic therapy with the primary tumor in situ . This result is an argument in favor of resection of the primary tumor, even when patients have little to no symptoms. Abstract : What's new? As the value of palliative primary tumor resection in stage IV CRC is still under debate, this nationwide population‐based study investigates if resection at initial treatment is associated with improved overall survival. In a recent cohort of 6, 091 patients, the authors show that elective palliative resection of the primary tumor is associated with improved overall survival in a multivariable Cox regression analysis. The effect persists after propensity score matching and in a landmark analysis predicting conditional survival including only patients who were alive at 6 months after diagnosis to correct for differences in short‐term outcomes due to intervention‐related mortality.